Changes in the microstructure of testicle in diabetes in the experiment. - I. I. Savka; E. E. Dzhalilova (Морфологія, 2016)
To study micro and microstructure of testis of white rat in norm and the under the condition of the streptozotozin-induced diabetes. Material and methods. The researches have been performed on 50 white mature male rats aged 4.5 to 7.5 months with body weight of 130 to 150g. Research material is represented by microscopic testicle slice. Experimental diabetes modelling was performed through single intraperitoneal injection of Streptozotocin (“Sigma”, USA), dissolved in 0.1M citrate buffer, pH=4.5 (7mg per 100g of body weight of animals). The diabetes mellitus progression was controlled according to glucose concentration in blood, which was measured by glucose oxidase test. Animals in whose blood glucose concentration in 2,4,6,8 weeks after launch of experiment was above 13.4 mmol/l were used for research. Results. The first signs of change angioarchitectonics testicular found 2 weeks of experimental diabetes. During the following terms blood stream undergoes significant changes. The lumen of the capillaries were narrowed, pericapillary spaces are dilated. Conclusion. Changing the diameter of the vessels microvasculature endothelial accompanied by swelling and changes in the form of their lumen, there is adhesion and aggregation of red blood cells.